Evaluation of Academic Supervision as an Effort to Strengthen the Internal Quality Assurance System in School - Widya Belqis Humairoh; Hasyim Asy’ari; Sita Ratnaningsih (Universitas Islam Negeri Walisongo, 2026)
Academic supervision plays an essential role in improving the quality of learning at SMP Negeri 3 Tangerang. This study aims to describe the implementation of academic supervision, its benefits in enhancing teacher professionalism, the supporting and inhibiting factors, and its contribution to strengthening the Internal Quality Assurance System through the cycle of Establishment, Implementation, Evaluation, Control, and Improvement. This research employed a descriptive qualitative approach by collecting data through interviews with the Vice Principal for Curriculum and a teacher. The findings indicate that academic supervision is carried out systematically through the stages of pre-observation, observation, and post-observation, providing significant feedback for improving teachers’ competence in lesson planning, classroom management, and reflective evaluation. Supervision also serves as a foundation for evaluating the implementation of SPMI standards. Supporting factors include school leadership, a collaborative school culture, and teacher enthusiasm, while inhibiting factors relate to limited time allocation and teachers’ perceptions of supervision. The study concludes that well-implemented academic supervision contributes to strengthening SPMI when conducted continuously, systematically, and collaboratively.